ANTIMICROBIAL ACTIVITY OF THE FIBER PRODUCED BY “POCHOTE” CEIBA AESCULIFOLIA SUBSP. PARVIFOLIA - Franco, B.M; Jiménez-Estrada, M.; Hernández-Hernández, A.B.; Hernández, L.B.; Rosas-López, R.; Durán, A.; RodrÃguez-Monroy, M.A.; Canales-MartÃnez, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The cotton-like fiber from the fruit of Pochote (Ceiba aesculifolia subsp. parvifolia) can be applied to wounds for healing purposes. As microorganisms can infect wounds and hamper the wound healing process, the aim of this study was to determine the antimicrobial activity and chemical composition of the methanolic extract of Pochote fiber. Materials and Methods: The methanolic extract was tested against bacteria and fungi. For bacteria, the Kirby-Baüer disc diffusion and broth dilution methods were employed to determine the MIC and MBC. In addition, bactericidal kinetic curves were generated. The antifungal activity was determined by the radial diffusion method. The antioxidant activity, total phenolic content, and the flavonoid content were determined. Bioassay guided fractionation was also performed. Results: The methanolic extract showed activity against Enterococcus faecalis, Staphylococcus aureus and Vibrio cholerae (cc). The tested V. cholerae strains were the most sensitive strains, and exhibited a clear CFU size reduction from the bactericidal kinetic curves. The methanolic extract had activity against T. mentagrophytes and R. lilacina . The antioxidant activity (SC50= 36.42 μg/mL) was related to the total phenolic (74.4 mg eAG/g) and flavonoid content (21.982 mg (eQ)/g). The bioassay guided fractionation results suggested that the antimicrobial properties of the extract may act through synergism because the total extract had higher activity against bacteria compared to the collected fractions. Conclusion: This study scientifically validates the application of the fruit fiber from Pochote as a part of a traditional medicine approach to alleviate infections caused by bacteria and fungi.